2021
DOI: 10.3126/nmcj.v23i1.36219
|View full text |Cite
|
Sign up to set email alerts
|

Tear Sample Analysis For SARS-COV-2 of Confirmed Cases of COVID-19

Abstract: Researchers in 2004 found that tear flim can be one of the modes of transmission of SARS-CoV. Considering the fact that SARS-CoV-2 is similar to SARS-CoV, it is speculated that there may be a risk of transmission through tear flim in patients with COVID-19. Therefore, this study was conducted to understand whether COVID-19 viral genome is present in the tear film or not. It was a cross-sectional quantitative study done in Kathmandu Medical College Teaching Hospital, Duwakot. Tear sample collection was done usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Rai et al [ 14 ] and Arora et al [ 15 ] found higher rates of positive results in tear samples reported at 23.33% and 24%, respectively. Conversely, Rodríguez-Ares et al [ 16 ] and Karimi et al [ 4 ] found lower rates at 7.1% and 7%, respectively, which closely align with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Rai et al [ 14 ] and Arora et al [ 15 ] found higher rates of positive results in tear samples reported at 23.33% and 24%, respectively. Conversely, Rodríguez-Ares et al [ 16 ] and Karimi et al [ 4 ] found lower rates at 7.1% and 7%, respectively, which closely align with our findings.…”
Section: Discussionmentioning
confidence: 99%